Repercussions of neck pain on the quality of life of health professionals in Intensive Care Units - de Oliveira Redü, Alberto; Modernel Xavier, Daiani; Amaral Daoud, Marcela; Calcagno Gomes, Giovana; Gomes Soares, Franciele; Garcia Lourenção, Luciano; Rieth Bennetti, Eliane Raquel (Investigación y Educación en Enfermería, 2024)
Objective. To analyze the repercussions of neck pain on the quality of life of health professionals in intensive care units. Methods. Cross-sectional, descriptive and correlational study, carried out with 94 health professionals (21 nurses, 13 physical therapists and 60 nursing technicians) in Intensive Care Units of two medium-sized hospitals in a municipality in the far south of Brazil. An instrument containing variables of sociodemographic and work environment characterization was applied; the Neck Bournemouth Questionnaire (NBQ) and the WHOQOL-Bref were applied. Results. There was a predominance of female professionals (88.3%), white (78.8%), aged 30 to 39 years (34.1%), with family income between one and two minimum wages (31.9%) and weekly workload between 31 and 40 hours (67%), night shift (54.3%), time of professional experience of one to five years (38.3%) and one job (73.4%). Neck pain and disability showed significant negative correlations with quality of life. The relationship was weak with the physical (r: -0.218; p=0.035) and psychological (r: -0.280; p=0.006) domains, and moderate with social relationships (r: -0.419; p<0.001), environment (r: -0.280; p<0.001) and general quality of life (r: -0.280; p<0.001). Overall quality of life showed a moderate correlation with the feeling of anxiety (r: -0.431; p<0.001) and depression (r: -0.515; p<0.001) of professionals in the last week. Conclusion. Neck pain caused repercussions in the physical, psychological, social, environmental and general quality of life of health professionals in intensive care units.